Analysis of the dynamics of child traumatism in Ukraine - L. O. Litvinova; O. M Donik; N. V. Grechishkin (Сучасні медичні технології)
Purpose of the study. To analyze the dynamics of childhood traumatism in Ukraine in 2012–2017, to investigate the main causes of child traumatism and to determine the leading ways of its prevention. Materials and methods. The data of the study became the data of the Center for Health Statistics of the Ministry of Health of Ukraine using basic